Pengaruh Customer Experiental Quality, Destination Image dan Novelty Seeking Terhadap Revisit Intention dan Customer Satisfaction sebagai Variabel Mediasi : Studi pada Konsumen Beranda Eatery Kebumen - Hengki, Hengki; Riptiono, Sulis (LP3M Universitas Putra Bangsa, 2023)
The purpose of this study was to analyze the effect of customer experiential quality, destination image and novelty seeking on revisit intention and customer satisfaction as mediating variables. Respondents in this study were 100 consumers of Beranda Eatery Kebumen. This study used descriptive and statistical analysis methods with the help of the SPSS 22 program. Statistical analysis used in this study were validity tests, reliability tests and path analysis. The results of this study indicate that customer experiential quality, destination image, and novelty seeking partially affect customer satisfaction and revisit intention. Customer satisfaction mediates the relationship between customer experiential quality, destination image, and novelty seeking towards revisit intention among consumers at Beranda Eatery Kebumen.